Xanthelasma Palpebrarum In A Young Adult Male Patient - Sinaga, Riana Miranda; Nahrisyah (Talenta Publisher, 2025)
ABSTRACT Background: Xanthelasma palpebrarum is a most common form of xanthoma characterized as lesion with yellowish colour, flat, soft, and mostly found in medial corner of eyelids. Most cases of xanthelasma are associated with hyperlipidemia. Case Reports: A male aged 37 presented with yellow patches on both upper eyelids since ±2 years ago. Vital sign within normal limid. Dermatological examination found yellowish plaques with clear boundaries sized 0.5 cm located on medial canthus of the supraorbital dextra and sized 1 cm located on medial canthus of the supraorbital sinistra. Laboratory test showed that hypercholesterolemia. The patient then underwent excision surgical procedure. Discussion: Xanthoma is a plaque consisted abnormal deposition of lipid and foam cells. Generally, this condition is found in aged 40–60 years old. The condition is found more in females than males, on superior palpebrae as the most common location. Diagnosis is established based on history and dermatological evaluation. The aim of xanthelasma management is mostly cosmetic-related. Elliptical or fusiform excision is the most method applied. Conclusion: A 37 years old male with xanthelasma palpebrarum on bilateral upper eyelids with hypercholesterolemia was treated with surgical excision. The surgical wound appeared well later on the 6th days and a month post-surgery. Latar Belakang: Xantelasma palpebrarum merupakan bentuk xantoma yang paling umum dengan lesi berwarna kekuningan, datar, lunak, dan sebagian besar terletak di sudut medial palpebra. Sering dikaitkan dengan hiperlipidemia. Laporan Kasus: Seorang laki-laki 37 tahun datang dengan bercak kekuningan pada kedua sudut kelopak mata atas sejak ±2 tahun lalu. Tanda vital dalam batas normal. Pemeriksaan dermatologis ditemukan plak berwarna kekuningan, dengan diameter berukuran 0,5 cm berbatas tegas pada regio kantus medial supraorbital dekstra dan 1 cm berbatas tegas pada regio kantus medial supraorbital sinistra. Pemeriksaan laboratorium menunjukkan kolesterol total 215 mg/dL, HDL 45 mg/dL, LDL 126 mg/dL, dan trigliserida 110 mg/dL. Pasien kemudian direncanakan untuk dilakukan bedah eksisi. Diskusi: Xantoma adalah plak yang terdiri dari endapan lipid abnormal dan sel busa. Umumnya kondisi ini muncul pada usia 40-60 tahun, ditemukan lebih banyak pada perempuan dibandingkan dengan laki-laki dan palpebra superior sebagai lokasi tersering. Diagnosis umumnya ditegakkan berdasarkan anamnesis dan pemeriksaan dermatologis. Penatalaksanaan xantelasma ditujukan untuk mengatasi gangguan kosmetik. Eksisi elips merupakan metode yang paling banyak digunakan. Kesimpulan: Seorang pria 37 tahun dengan xantelasma palpebrarum pada palpebra superior bilateral dengan hiperkolesterolemia ditangani dengan bedah eksisi. Luka tampak baik saat kontrol 6 hari dan satu bulan pasca tindakan.